(untitled) (Research, Society and Development, 2022)
The limestone reaction is limited to the place of its application in the soil, so there are doubts about its efficiency in reducing acidity in depth when applied superficially without incorporation. Therefore, the objective of this work was to analyze the movement and residual of different doses of lime in the soil profile and its influence on soybean grain productivity. The experimental design used was randomized blocks with six treatments and four replications. The limestone was applied manually by haul, without incorporation. One month after the planting of soybeans, the yield of each treatment was estimated. After harvesting, soil sampling was done at three depths for chemical analysis. In the following year, soybean planting and the same evaluations were carried out again. The data obtained were subjected to analysis of variance and when significant, the means were compared using the Tukey test. There was a residual effect, movement and better efficiency of the limestone in the soil profile from the application of the recommended dose. Grain productivity increased as the percentages of the recommended dose of limestone increased in the first harvest, in the following harvest it showed better productivity in the recommended dose.